A Rare Entity of Benign Recurring Mesenchymal Tumor of the Female Urethra. (18th September 2013) - Telli, Onur; Sarıcı, Haşmet; Özgür, Berat Cem; Yücetürk, Cem Nedim; Karagöz, Mehmet Ali
Abstract : This is a case report of a 51-year-old female patient with benign mesenchymal tumors of paraurethral region which caused lower urinary tract symptoms. The pathological examination of the lesion was reported as angiomyxoma which is a distinct soft tissue tumor characterized by the presence of prominent myxoid matrix and numerous thin-walled blood vessels. This tumor has a predilection for the trunk, head and neck, extremities, and genitalia. It is a benign tumor, and total excision is curative. Recurrence is rare except for aggressive angiomyxomas.